Feasibility Study of Aluminum Ingot Manufacturing Plant Development Using Latest Technology with Aluminum Scrap Raw Material and 50,000 TPY Capacity in Cilegon Industrial Area - Dedy Setyo Oetomo; Farliana Sutartiah; Akhsani Nur Amalia (Jurnal Teknologika, 2025)
This study presents a comprehensive feasibility analysis for establishing an aluminum ingot manufacturing plant in Cilegon Industrial Area, Indonesia, with a production capacity of 50,000 tons per year (TPY) using aluminum scrap as primary raw material. The study encompasses demand assessment for the Indonesian market, supply chain analysis for both raw materials and finished products, evaluation of latest processing technologies, detailed capital expenditure (CAPEX) and operational expenditure (OPEX) calculations, and investment scheme analysis with 60% debt financing and 40% equity investment. The research methodology includes market analysis, technology assessment, financial modeling, and risk evaluation following aluminum smelting industry standards. Results indicate strong market demand with projected growth of 8.5% annually, adequate raw material supply from domestic and regional sources, and competitive advantages through modern reverberatory furnace technology with electromagnetic stirring systems. The total CAPEX is estimated at USD 45.2 million, with annual OPEX of USD 28.7 million. Financial analysis reveals positive net present value (NPV) of USD 12.8 million, internal rate of return (IRR) of 18.2%, and payback period of 6.8 years, confirming project viability. The study concludes that the proposed aluminum ingot plant demonstrates strong commercial and technical feasibility, with robust returns exceeding industry standards and strategic positioning in Indonesia's growing aluminum market